Three‐dimensional metal‐only phoenix cell and its application for reflectarrays - Zhihang An; Tony Makdissy; María Garcia Vigueras; Sébastien Vaudreuil; Raphaël Gillard (IET Microwaves, Antennas & Propagation, 2024)
Abstract A 3D metal‐only waveguide‐based phoenix cell for reflectarray is presented. The proposed cell consists of two concentric square waveguides and a metallic block in the centre, which offers two operation modes. The first mode uses its cross section to tune reflection phase while the second mode varies the heights of two waveguides to manipulate reflection phase. The principle of the two different modes is analysed in detail. A metal‐only reflectarray antenna at 20 GHz is designed based on the first mode of the phoenix cell. It is fabricated using selective laser melting 3D printing technology. A good agreement between simulations and measurements is achieved. The measured gain at 19.75 GHz is 30.25 dBi with an aperture efficiency of 51.17% respectively. Also, the measured 1‐dB gain bandwidth is 15% (19–22 GHz). A dual band metal‐only reflectarray operating at 20 and 25 GHz is designed based on the second mode of the phoenix cell. The two metal‐only reflectarray antennas fully demonstrate the capabilities of the proposed 3D metal‐only phoenix cell.